Towards Rational Design Method for Strengthening of Concrete Structures by External Bonding - Ueda, T.; Zhang, D.; Furuuchi, H. (Civil Engineering Dimension, 2012)
Many infrastructures need to be repaired or strengthened due to various reasons, such as unexpected deterioration and changes in performance requirement. This paper presents the following recent achievements by the authors’ group on design method for flexural strengthening of concrete structures by external bonding; (i) fracture characteristics of interface between substrate concrete and cementitious overlay, (ii) crack spacing of flexural strengthened beams, which affects debonding strength, (iii) strengths of intermediate crack (IC) debonding and end peeling, (iv) strength of concrete cover separation, and (v) effectiveness of strengthening by external bonding. A unified approach for flexural strengthening by steel plate, fiber reinforced polymer lami¬nate and cementitious overlay, for both intermediate crack (IC) debonding, including end peeling, and concrete cover separation is pre¬sented with consideration of crack spacing in the streng¬thened members. Appropriate interfacial rough¬¬¬ness to achieve efficient interface bond property is clari¬fied and the concept of effectiveness of strengthen¬ing is proposed for better strengthening design.